Peripartum Covid-19 Pneumonia with Severe ARDS – A Case Report - Maier, Josefine Theresia; Zickler, Daniel; Metz, Melanie; Jebens, Anja; Jarchau, Ute; Fischer, Julia; Kimmel, Viktor; Prueter, Eric; Hellmeyer, Lars (Zeitschrift für Geburtshilfe und Neonatologie, 2021)
Introduction SARS-CoV-2 is a novel coronavirus that was first isolated in Wuhan, China, and resulted in a rapidly spreading pandemic worldwide. Currently there is only limited evidence on the effect of COVID-19 on pregnant women.Case Here we present one of the first serious COVID-19 cases in pregnancy at term with subsequent delivery. Postpartum the mother required antibiotic and symptomatic treatment. She experienced acute worsening of symptoms and developed acute respiratory failure requiring endotracheal intubation and subsequently extracorporeal membrane oxygenation.Conclusion COVID-19 affects all medical disciplines, requiring interdisciplinary approaches and development of patient care regimes. Obstetricians should be aware and be prepared for the special needs of pregnant women with potential prenatal and postnatal issues. Ideally pregnant COVID-19 patients should be cared for at a tertiary perinatal center with experienced perinatologists and neonatologists.
Keywords: COVID-19; SARS-CoV-2; peripartum COVID-19; ECMO; ARDS; pregnancy COVID-19